2020
DOI: 10.1093/pcp/pcaa162
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Contributes to the Quality Control of Leaf Mitochondria

Abstract: In autophagy, cytoplasmic components of eukaryotic cells are transported to lysosomes or the vacuole for degradation. Autophagy is involved in plant tolerance to the photooxidative stress caused by ultraviolet B (UVB) radiation, but its roles in plant adaptation to UVB damage have not been fully elucidated. Here, we characterized organellar behavior in UVB-damaged Arabidopsis (Arabidopsis thaliana) leaves and observed the occurrence of autophagic elimination of dysfunctional mitochondria, a process termed mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 84 publications
0
31
0
Order By: Relevance
“…The vector containing the UBQ10 :: GFP-ATG8a construct (At4g21980.1 [ 72 ]) was transformed into the A. tumefaciens strain GV3101, which was subsequently used to transform Arabidopsis via the floral dip method. T 1 plants were selected for their ability to grow on Basta-soaked soil and propagated to the next generation.…”
Section: Methodsmentioning
confidence: 99%
“…The vector containing the UBQ10 :: GFP-ATG8a construct (At4g21980.1 [ 72 ]) was transformed into the A. tumefaciens strain GV3101, which was subsequently used to transform Arabidopsis via the floral dip method. T 1 plants were selected for their ability to grow on Basta-soaked soil and propagated to the next generation.…”
Section: Methodsmentioning
confidence: 99%
“…What is implied here is that in the cell cycle is a type of surveillance mechanism for mitophagy. However, mitophagy and its regulation have been predominantly investigated in the context of a range of stressors, such as UV light [ 80 ], and senescence [ 76 , 77 , 78 , 79 ]. Interestingly, recent work has implicated the FRIENDLY protein, linked to mitochondrial fusion because of its clustering role, in mitophagy.…”
Section: Massive Mitochondrial Fusion In the Plant Life Cyclementioning
confidence: 99%
“…During their life cycle, plants are also subjected to longer or shorter photoperiods depending on the seasons but also to variable light spectral qualities including visible light (400–700 nm) and ultraviolet-B (UV-B; 280–315 nm), the most energetic wavelength light reaching the surface of the Earth [ 66 , 67 ]. A strong and prolonged exposure to either visible light or UV-B can lead to large damage of plants macromolecules (DNA, proteins and lipids).…”
Section: Autophagy a Series Of Intense Membrane Remodeling Events Controlling Plant Responses To Environmental Stressesmentioning
confidence: 99%
“…A strong and prolonged exposure to either visible light or UV-B can lead to large damage of plants macromolecules (DNA, proteins and lipids). Recently it was shown that the atg2 , atg5 , atg7 , atg10 , atg12a, and atg18a mutants were hypersensitive to a treatment with UV-B leading to a half reduction in the activity of PSII in comparison with the WT [ 66 , 67 ]. A high visible light treatment also induced a necrosis phenotype in the atg2-1 mutant [ 60 ].…”
Section: Autophagy a Series Of Intense Membrane Remodeling Events Controlling Plant Responses To Environmental Stressesmentioning
confidence: 99%